Effects of double JPEG compression on steganalysis - Ya-Feng Zhou; Ng, W. W. Y.; Zhi-Min He (2012 International Conference on Wavelet Analysis and Pattern Recognition, 2012)
Double compression is quite common due to image forgery and specific steganographic algorithms. It would notably impact results of steganalysis if not treated properly. This paper discusses the effects of double compression to steganalysis. Then, we evaluate the effect of double compression using L-GEM based RBFNN in comparison to widely adopted SVMs.